E-wallet: factors influencing user acceptance towards cashless society in Malaysia among public universities - Norulhuda Abdullah; Fauziah Redzuan; Nor Aziah Daud (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The evolution of financial technology into digital payment has led to a new era of cashless society. In line with the global trend, the Malaysian Government has been committed to strengthen the agenda of a cashless society by actively promoting the use of e-Wallet through the establishment of the interoperable credit transfer framework (ICTF) policy in 2018. Although e-Wallet has been implemented since 2016, several previous studies have found that the level of acceptance is still relatively low while the main factors that influence the acceptance of e-Wallet in Malaysia still remain unclear. This study aims to identify the factors that influence the acceptance of e-Wallet towards establishing cashless society in Malaysia. Online survey using closed-ended questionnaires have been conducted among 400 respondents from students and employees of Malaysian public universities in Klang Valley. Collected data have been analyzed using descriptive statistics and inferential statistics which consist of Factor Analysis, Pearson Correlation and Multiple Linear Regression in statistical package for the social sciences (SPSS). Based on the findings, four factors are found to significantly influence e-Wallet acceptance, which consist of performance expectancy (PE), social influence (SI), facilitating conditions (FC) and trust (T). facilitating conditions (FC) is the most influential significant factor behind the acceptance of e-Wallet among Malaysians.